I am starting to learn how to solve differntial equations. Can someone tell me how I can solve the following equation?

I have the following equations:

C1’(t) = -(F/V1) * C1(t)

C2’(t) = (F/V2) * {C1(t) – C2(t) }

Initial conditions are:

C1(0) = 0.1/V1

C2(0) = 0

It seems that the solution must be :

C2(t) = {Q1(0) / (V1 – V2) } * {e –(F/V1)t – e–(F/V2)t }

Can someone explain me in detail how I have to calculate to reach this solution ? In my course book Bernouilli's method is mentioned but I do not understand it ...